SOCJOLOGIA MORALNOŚCI MARII OSSOWSKIEJ W OPINII WYBRANYCH ŚRODOWISK KATOLICKICH - Mariański, Janusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In Poland, the development of the sociology of morality is related to Maria Ossowska’s scholarly activities. She studied social facts in the context of morality, describing and explaining all that, which in the opinion of people, belongs to realm of morality. Ossowska did not practice normative ethics, but the science of morality, postulating its assumptionlessness. Ethicists who stemmed from Catholic circles demanded that along with the science of morality scientific-normative ethics should also be cultivated. Polemics with Ossowska were fragmentary in character and appeared in the works of some ethicists and sociologists. Catholic ethicists primarily probed the problems of normative ethics. The paper presents the stance of the Catholic ethicists and sociologists of the 1980s and 90s, towards some of Maria Ossowska’s writings.